Topsoe Wet Gas Sulphuric Acid (WSA) Technology - An Attractive Alternative For Reduction Of Sulphur Emissions From Furnaces And Converters - H. Rosenberg (The Southern African Institute of Mining and Metallurgy, 2006)
Haldor Topsoe A/S has developed its WSA technology to meet the demand in the market for a simple and reliable process that converts sulphurous emissions from off-gasses into high-grade sulphuric acid. With more than 50 references in 25 countries, the WSA technology has proven its ability to generate acid at 98% concentration, efficiently and economically. The wet gas sulphuric acid (WSA) technology treats the furnace off-gas directly from upstream gas cleaning plants. No further drying is required, since the humidity present in the off-gas is used to hydrate the SO3generated in the converter and produce sulphuric acid. The heat generated during the oxidation, hydration and condensation processes is principally reused in the process to preheat the off-gas to the required temperature level, and also to generate high pressure superheated steam for process use. This advantage of steam production, coupled with lower water and power consumption requirements, is particularly important in the African production environment. Having fewer process components than conventional acid plants, the WSA technology is a simple and compact operation, which makes it easier to retrofit into an existing smelter plant. Further, the WSA technology simultaneously offers the possibility to treat multiple gas streams arising within the production facility due to superior flexibility in terms of SO2concentration and turndown ratio.